Social innovation, social enterprise, and local public services: Undertaking transformation?. (8th February 2018) - Sinclair, Stephen; Mazzei, Micaela; Baglioni, Simone; Roy, Michael J.
Abstract: This article discusses some of the challenges encountered in embedding effective and sustainable social enterprise and social innovation within established political institutional systems to deliver local welfare services. It draws upon evidence analyzing social innovation and social enterprise in Scotland to contribute to the debate over whether social innovations and social enterprises are able to meet expectations in addressing the significant challenges faced by welfare systems. The article clarifies the meaning of both these contested concepts and explains how social innovation and social enterprise relate to similar ideas in social and public policy. The evidence suggests that actually operating social enterprises and social innovations do not embrace the image of them promoted by enthusiasts as either "entrepreneurial" or "innovative". Furthermore, they bring distinctive challenges in delivering local welfare services, including potential tensions or rivalry with existing public agencies. The article suggests that social enterprises and social innovations are not themselves instigators nor catalysts for systemic change, but that their impact is constrained by structural conditions and institutional factors beyond their control.